subtract:%20(3b%E2%88%922c)%E2%88%92(6c+2b)%E2%88%92(b+c)%20.(1%20point

1 answer

To simplify the expression \((3b - 2c) - (6c + 2b) - (b + c)\), we can follow these steps:

  1. Distribute the negative signs to each term in the parentheses: \[ = 3b - 2c - 6c - 2b - b - c \]

  2. Combine like terms:

    • For the \(b\) terms: \(3b - 2b - b = 0b = 0\)
    • For the \(c\) terms: \(-2c - 6c - c = -9c\)

Putting it all together, we get: \[ 0 - 9c = -9c \]

Thus, the simplified expression is: \[ \boxed{-9c} \]